Dukungan Orang Tua, Motivasi Dan Sarana Transportasi Belajar Terhadap Kedisiplinan Siswa SMK Negeri 2 Purwodadi - , KARSULIS, Prof. Dr. Sutama, M.Pd, Dr. Suyatmini, M.Si (2017)
Karsulis. Q 100 15 0025, The Contribution of Parents, Motivation and Transportation Learning Toward The Discipline of The Students at SMK N 2 Purwodadi. Tesis. Pascasarjana Universitas Muhammadiyah Surakarta. 2017. The objectives of this research are to analyze the contribution of parents, motivation and transportation learning toward the discipline of the students at SMK N 2 Purwodadi both simultan eously and partially. The kind of this research is quantitative research. The research was conducted at taken 313 respondents as the research sample with proportional random sampling technique. Techniques of data collection used questionnaires. Technique of analyzing data used multiple linear regression analysis, accuracy test model, accuracy test estimation parameter, donations predictor and classical assumption. The results of this study state that the contribution of parents, motivation and transportation learning simultan eously have contributed to the discipline of the students at SMK N 2 Purwodadi with α 5 % is 0,434. The score of significant level is 0.000 < 0.05. The relative contribution of parents is 7,9 %, Motivation of learning is 52,1 % and Transportation of learning is 40 %. The total of effective contribution is 18,8 % : The contribution of parents is 1,5 %, Motivation of learning is 9,8 % and Transportation of learning is 7,5 %.